Dietary Patterns of Adults in Québec and their Nutritional Adequacy - Beaudry, Micheline (Can J Public Health, 1998)
The purpose of this study was to identify dietary patterns among adults in Québec and to determine their relationship to nutritional adequacy of the diet. We used 24-hour food recall data on 2,104 adults from the Québec nutrition survey (1990). Nutritional adequacy was assessed based on the 1990 Nutrition Recommendations for Canadians; dietary patterns were assessed via a factor analysis of the 30 food groups consumed. The three major patterns identified (‘high-energy density’, ‘traditional’ and ‘health-conscious’) explained 18% of the variation in food intake. Only the ‘health-conscious’ pattern correlated positively with the four chosen indicators of nutritional adequacy. Generally, men scored positively on the ‘high-energy density’ and the ‘traditional’ pattern whereas women scored positively on the ‘health-conscious’ pattern. Aside from sex, scoring was most related to age and education. The use of these patterns to define and target nutrition interventions should be tested in the aim of improving the effectiveness of health promotion.